(3QSGdI aj GdGSJYGQIs - (3GdWHdGhj , efUhQ GdWHdGhj Hf SHW fGUQ GdOjf eMeO Hf SGde, SHW fGUQ GdOjf,J (B1014 (3g` s
(3BNQgG (B:s
(3hGdcdGe Ydi gPjf GdHjJjf eYdhe eYQha s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B15s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3HdGZI (B119) s
Keywords: (3GdHdGZIs